“Good breast” mothers. Representation of patriarchy in Cristina Peri Rossi’s “Desastres íntimos” - De la Barra Van Treek, Erika (Árboles y Rizomas, 2022)
This paper analyses the short story "Desastres íntimos" by the Uruguayan writer Cristina Peri Rossi from both a decolonial feminist perspective and the conception of the body. The analysis is structured from three fundamental perspectives. Firstly, the notion of patriarchy and the masculine world in which the protagonist is involved: her relationships with Antonio, her son Andrés, her boss and her psychoanalyst. Secondly, the relationship that the protagonist establishes with her maternal role and the contradiction in which she lives her motherhood and professional development, challenging the pseudo-feminist idea of the super mother. Finally, the relationship she establishes with her own body and sexuality, understanding that this is a political space of domination and struggle for her own rights. The main findings show that the protagonist lives an explicit patriarchal oppression experienced through the male characters and especially through her role as mother/professional, which is overturned at the end of the story.